A Hybrid Security Algorithm AES and Blowfish for Authentication in Mobile Applications - Purwinarko, Aji; Hardyanto, Wahyu (Scientific Journal of Informatics, 2018)
Nowadays, everything is within our grasp and with the mobile phones become easier. Its use is not limited to calls and SMS but has become a tool that can be used to serve business transactions, banking, academic of data through mobile applications. Tus, the security of authentication in the mobile application needs to be improved to avoid a hacker attack. This article presents an authentication in the mobile application to the server using a hybrid of cryptographic algorithm Advanced Encryption Standard (AES) and Blowfish. AES and Blowfish is a symmetric key algorithm is very fast and powerful. With the utilization of a large block size of AES and Blowfish to encrypt keys, AES security will be much more robust and complicated to attacked. So, it will be difficult for hackers to perform Man in the Middle (MitM) attacks.